Endoscopic ultrasound-guided gastrojejunostomy with a lumen-apposing metal stent: a multicenter, international experience - Tyberg, Amy; Perez-Miranda, Manuel; Sanchez-Ocaña, Ramon; Peñas, Irene; de la Serna, Carlos; Shah, Janak; Binmoeller, Kenneth; Gaidhane, Monica; Grimm, Ian; Baron, Todd; Kahaleh, Michel (Endoscopy International Open, 2016)
Background: Surgical gastrojejunostomy and enteral self-expanding metal stents are efficacious for the management of gastric outlet obstruction but limited by high complication rates and short-term efficacy. Endoscopic ultrasound-guided gastrojejunostomy (EUS-GJ) is a novel alternative option. Patients and methods: Patients who underwent EUS-GJ between March 2014 and September 2015 as part of a prospective multicenter registry at four academic centers in two countries were included. Technical success was defined as successful placement of a gastrojejunal lumen-apposing metal stent. Clinical success was defined as the ability of the patient to tolerate an oral diet. Post-procedural adverse events were recorded. Results: The study included 26 patients, of whom 11 (42 %) were male. Technical success was achieved in 24 patients (92 %). Clinical success was achieved in 22 patients (85 %). Of the 4 patients in whom clinical success was not achieved, 2 had persistent nausea and vomiting despite a patent EUS-GJ and required enteral feeding for nutrition, 1 died before the initiation of an oral diet, and 1 underwent surgery for suspected perforation. Adverse events, including peritonitis, bleeding, and surgery, occurred in 3 patients (11.5 %). Conclusion: EUS-GJ is an emerging procedure that has efficacy and safety comparable with those of current therapies and should hold a place as a new minimally invasive option for patients with gastric outlet obstruction.Clinical trial identification number: NCT01522573